Reconstruction of chronic triceps tendon avulsion using synthetic mesh graft in a dog - Ambrosius, L.; Arnoldy, C.; Waller, K. R., III; Little, J. P.; Bleedorn, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Avulsion of the triceps tendon insertion was diagnosed in a two-year-old Poodle mixed breed dog 10 weeks after traumatic injury. Diagnosis was confirmed with clinical examination and magnetic resonance imaging (MRI). The tendon was reconstructed using tension-relieving sutures augmented with a synthetic degradable porous polyurethane urea onlay mesh graft. The repair was immobilized using a transarticular external skeletal fixator with staged increases in elbow flexion. Treatment was successful, with signs of healing confirmed by MRI and normal clinical function one year after surgery. The successful outcome in this case suggests that surgical repair of a chronic triceps tendon injury using a synthetic mesh augmentation may be successful in similar cases.
Keywords: Dog; tendon; avulsion; graft; Artelon®